Generalized Status Harary Based Indices - Harish, N.; Chaluvaraju, B. (The Nepali Mathematical Sciences Report, 2023)
In this article, we initiate the study of generalized status Harary based indices such as k-sum status Harary index, k-product status Harary index and k-difference status Harary index of a non-trivial, undirected, simple connected graph, where k is a positive integer. Here many bounds of the generalized status Harary based indices are obtained and its exact values for some specific families of graphs are found. Also, its relationship with other graphical indices are investigated. In addition that, we explore the comparative analysis of the molecular graphs of paraffin hydrocarbons.